2016
DOI: 10.19175/recom.v6i3.994
|View full text |Cite
|
Sign up to set email alerts
|

Adesão ao tratamento antirretroviral: uma intervenção multiprofissional

Abstract: RESUMOObjetivo: relatar a experiência de residentes multiprofissionais na intervenção realizada aos usuários e profissionais da saúde, a partir dos resultados de pesquisa que verificou fatores que dificultam a adesão ao tratamento antirretroviral entre indivíduos em tratamento para a Síndrome da Imunodeficiência Adquirida. Métodos: trata-se de um relato de experiência, no qual usuários não aderentes, acompanhados no ambulatório de adesão de um Hospital Universitário e de um Centro de Testagem e Aconselhamento,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 5 publications
0
3
0
6
Order By: Relevance
“…Regarding the positive factors, it is remarkable the word quality of life, according to authors, the Family Health Unity is a space that aims to guarantee the health caring to the users and promote life quality [ 25 ], seen that the professionals are responsible for by the TARV treatment and essentials on the empowering of the patients searching for information in a critical and constructive way about their health status and ways to improve the life quality importance, in addiction to have to role to aware that the adherence is extremely important to a long life with more quality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the positive factors, it is remarkable the word quality of life, according to authors, the Family Health Unity is a space that aims to guarantee the health caring to the users and promote life quality [ 25 ], seen that the professionals are responsible for by the TARV treatment and essentials on the empowering of the patients searching for information in a critical and constructive way about their health status and ways to improve the life quality importance, in addiction to have to role to aware that the adherence is extremely important to a long life with more quality [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of adherence is considered a threat to the effectiveness of the treatment, which contributes to the spread of virus-resistance (COLAÇO, 2016;MIYADA et al, 2017). It is also noticed that the correct use of ART can reduce the costs of future hospitalizations due to complications of the infection, as well as the need to exchange the medication for more complex and expensive ones (BANDEIRA et al, 2016;MENEZES et al ., 2018). Given the above, it is observed that adherence to treatment with ART requires more investigations to develop a care plan (VALE et al, 2018), in which the various factors involved are considered to better guide the multiprofessional and FPVHA team Depending on the way that PLWHA react in relation to their HIV status, they may show feelings of inferiority due to the discrimination suffered, uncertainty about the future, fear of approaching death and changes in appearance (ANTELMAN et al, 2007;GONZALEZ et al, 2011), which results in an unfavorable prognosis, with a greater involvement of opportunistic diseases, which can lead to neurocognitive impairments (CHRISTO, 2010;SEIDL et al, 2007;AZEVEDO et al, 2014) Anxiety and depression affect PLWHA twice or more than in the general population (PINTO et al, 2007), however, when both are treated, they show a high rate of improvement, reducing the use of health care, mortality and can prolong life (PINTO et al, 2007).…”
Section: Brief Contextualization Of Hiv/adsmentioning
confidence: 99%
“…Caso contrário, o aparecimento de alterações metabólicas endócrinas, como lipodistrofia, elevação da pressão arterial sistêmica e dislipidemia também contribui para a não adesão. Esse fato pode implicar tratamentos mais complexos e associados, com possibilidades para outros eventos e interações adversas, exigindo novas adaptações na rotina e estilo de vida, com prováveis implicações negativas no processo de adesão (14)(15) .…”
Section: Métodounclassified